The temporal characteristics of the TeV γ-emission from Mkn 501 in 1997 - Aharonian, Felix A.; Akhperjanian, A. G.; Barrio, J. A.; Bernlöhr, Konrad; Bojahr, H.; Calle, I.; Contreras, J. L.; Cortina, J.; Daum, A.; Deckers, T.; Denninghoff, S.; Fonseca, V.; et al. (Astronomy and astrophysics, 1999)
We present the results on the TeV gamma emission from Mkn 501 in 1997 obtained with the stand-alone Cherenkov telescopes CT1 and CT2 (threshold ≥ 1.2 and ≥ 1.0 resp.) of the HEGRA collaboration. The CT1 lightcurve has the most complete coverage of all TeV observations of Mkn 501 in 1997 due to the additional observations made under the presence of moonlight. CT2 - at the time of these observations a second generation Cherenkov telescope with relatively low imaging resolution - is a well tested instrument and its 85 hours of observational data on Mkn 501 in 1997 are useful for consistency checks and provide some additional daily data points. The Mkn 501 lightcurve data show signiﬁcant correlation with the RXTE ASM X-ray data consistent with no time-lag. The spectral analysis shows a steepening spectrum extending beyond 10 TeV. No change of the spectral slope with the variation of the intensity was found. The results presented here are consistent with the results from the HEGRA Cherenkov telescope system presented in part I of this paper.
Gesehen am 24.11.2020